Feeding Rate of Soil Animals in Different Ecosystems in Pati, Indonesia - RAHAYU WIDYASTUTI (HAYATI Journal of Biosciences, 2006)
The feeding activity of soil animals was measured by using bait lamina test in three main ecosystems, i.e. the teak forest, home garden and rainfed paddy field. Two additional ecosystems in rainfed paddy field, i.e. the old (permanently established bund around paddy fields) and new bunds were examined as well. Three blocks of bait-lamina sticks (each block consisting of 16 individual sticks) were exposed at each location. The bait lamina were retrieved from the soil after two days and visually assessed. Each hole is designated as Ã¢â‚¬Å“fedÃ¢â‚¬Â (perforated) or Ã¢â‚¬Å“non-fedÃ¢â‚¬Â hole. The feeding rate is measured as the absolute number of Ã¢â‚¬Å“fedÃ¢â‚¬Â holes. Soil animals in the old bunds showed the highest feeding activity (55.20%), followed by home garden (39.10%), rainfed paddy field (16.50%), teak forest (15.60%), and new bund (7.80%). The frequency of animals attack to the bait strips also indicated the similar pattern as their feeding activity, i.e. high in the old bunds (0.90), followed by home garden (0.70), teak forest (0.40), new bunds (0.40) and rainfed paddy field (0.30), respectively. Key words: soil animals, feeding activity, bait-lamina test